Multifunctional saving box / Muhammad Alman Zulkifli, Muhd Muslim Mohd Aruwa and Nur Izzati Izam - Zulkifli, Muhammad Aiman; Mohd Aruwa, Muhd Muslim; Izam, Nur Izzati (2013)
Nowadays, the children do not like to have the coin saving. This is because they do not know the value of the coin. This project namely as Multifunctional Saving Box. It created for encourage the children to saving the coin. The Multifunctional Saving Box can encourage the children to have the saving of coin with the sound that produce from the recorded and the lighting that produces from LED. With this output, the children will be more interest to saving the coin. When the coin is inserting, i-Box will display thank you in the short form there is “TQ”. In the Multifunctional Saving Box, there have are three slot of coin. The coin that insert will divide into its own slot. Each slot only can display the quantity of the coin from 0 until 99 when the coin was inserted.